Management of Religious Character Guidance for Early Childhood Education in Raudhatul Athfal Wonosobo - Hikmat Zakky Almubaroq (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
Islamic religious education is education that is used as a human foundation to build a spiritual soul in the series. In addition, religious education will also improve human morals for the better. Islamic religious education is an education that must be intensified in the negative influence of the progress of globalization. Early childhood education is an important education, because early childhood is a generation that is still easy to accept all events and events. Thus the researchers carried out research on the management of religious character guidance at the early childhood level at RA Hidayatussyiban Lancar, Wadaslintang. The research was carried out with descriptive qualitative methods, and was supported through data collection techniques of observation, interviews, and documentation. And then the data is analyzed by data reduction, data display, and drawing conclusions. Through the techniques carried out, data were obtained related to the management of religious character guidance at RA Hidattusyiban which showed the results that the organization carried out in RA in the learning category was carried out with a cooperative pattern by RA teachers. Then as for the organization in the categories of programs consisting of: 1) Al-Qur'an Reading and Writing Program, 2) Islamic Story Program, 3) Knowing Arabic Program, 4) Worship Practice Program. The implementation stages found were through habits consisting of: 1) memorizing prayers and short letters, 2) praying and practicing ablution, 3) reading the Koran, and 4) Islamic stories. The evaluation stages carried out by the teacher are: 1) socialization to parents of students, 2) evaluation of children's abilities after following the applied learning.